Konsentrasi Dan Distribusi Karbon Organik Total (TOC), Total Nitrogen (TN) Dan Rasio C/N Pada Sedimen Di Perairan Kawasan Pelabuhan Pangkal Balam, Bangka - Lara Sukma Sadewi; Mohammad Agung Nugraha; Irma Akhrianti (Journal of Tropical Marine Science, 2022)
Total organic carbon (TOC), total nitrogen (TN) and C/N ratio are organic matter present in the waters. The waters of Pangkal balam port area has a fairly dense community activity such as ports, aquaculture, PLTU and settlements. The waste from the activity enters the water column so that it can affect the abundance of the waters, therefore research on organic matter needs to be carried out in the waters of the Pangkal Balam Port Area. This study aims to determine the distribution pattern of TOC, TN and sediment C/N ratio in the waters of the Pangkal Balam Port Area. Knowing the source of organic matter input in the waters of the Pangkal Balam Port Area and knowing the relationship between TOC and fine sediment. Determination of research stations using stratified purposive sampling method. The sampling time was carried out in February 2021 in the waters of the Pangkal Balam Port Area, Bangka. TOC and TN concentrations were analyzed using the Walkley Black method and the Kjeldahl method. The TOC concentration ranges from 0.59-9.79% which is categorized as low to high, while the TN concentration scores between 0.01-0.06% which is classified as low to high and the C/N ratio is and 59-244.75 which is explain the main source of organic material input from terrestrial. TOC with fine sediment has a positive relationship and a weak effect (r = 0.472) and the coefficient of determination (R2) is 0.223%.